Effect of Wheat Germ, Wheat Germ Oil on Lipid Profile of Hypercholesterolemic Rats - Ghada Z A Soliman (International Journal of Lipids, 2020)
Hypercholesterolemia plays an important role in atherosclerosis and cardiovascular diseases (CVD) that represent one of the greatest worldwide medical problems nowadays. Recently, an increased attention/ interest for natural antioxidant/ hypercholesterolemia as WG/WGO is increasing. Wheat germ/ Wheat germ oil (WG/WGO) is an excellent source of essential and polyunsaturated fatty acids and vitamin E. It is one of the richest natural sources of tocopherol. This work aims to evaluate the effect of administration of wheat germ (WG) /wheat germ oil (WGO) for 6 weeks on serum lipid profile, lipid peroxidation (liver malondialdehyde) in hypercholesterolemic rats. One hundred and twenty maleSprague Dawelyrats weighing 180-192 gm were used in this study. They were randomly distributed into six groups (20 rats/ group) as follow: g1: normal control, G2: hypercholesterolemic rats; G3: Normal rats treated with WG; G4: hypercholesterolemic rats treated with WG; G5: Normal rats treated with WGO; G6: hypercholesterolemic rats treated with WGO for 6 weeks. Also WG was analysed for its nutritive value, while WGO was analysed for fatty acid profile, and studied for its physico-chemical properties. The results showed significant elevation of liver malondialdehyde (MDA) and serum lipid profile in untreated rats fed on hypercholesterolemic diet. Hypercholesterolemic rats treated with WG/WGO showed an improvement in the biochemical assay of their lipid profile compared with untreated hypercholesterolemic rats. WG/WGO may be able to protect against atherosclerosis and CVD. The administration of WG /WGO to diets of rats caused a marked reduction in TC, LDL-C, VLDL-C, TG and MDA. This improvement effect may be mediated via enhancement of the antioxidant defence system and other factors. However, further clinical studies on human beings are required to assess the efficacy and safety of the WG/WGO.
Keywords: Hypercholesterolemia